Slums: Uncovering Urban Problems and Challenges - Lasaiba, Mohammad Amin (JENDELA PENGETAHUAN, 2024)
Slum settlements represent a complex social and economic issue many countries face worldwide. This research aims to provide a comprehensive insight into the challenges of slum settlements. The study employs a literature review method to understand the context of slum settlement issues deeply. The research findings highlight that slum settlements are a complex global challenge many countries face, driven by rapid urbanization and high levels of economic inequality. Cooperation between governments, the private sector, and civil society organizations is crucial to address these challenges. Governments play a key role in designing policies, allocating resources, and monitoring slum improvement programs. Through effective collaboration between governments, the private sector, and civil society organizations, holistic and sustainable solutions are expected to improve housing conditions, facilitate access to basic services, and enhance the quality of life for urban residents, with the ultimate goal of sustainably eradicating slum settlements.